Description of a new orb-weaving spider species representing the first record of Novaranea in Australia (Araneae: Araneidae: Araneinae) - Framenau, Volker W. (Zootaxa, 2011)
The orb-weaving spider genus Novaranea Court & Forster, 1988, previously known only from New Zealand, is here reported from Australia for the first time with the description of a new species. Generic affinities, here based on characteristic shapes of the median and terminal apophyses of the male pedipalp, remain somewhat ambiguous as some of the endemic New Zealand araneine genera remain to be tested within a rigorous phylogenetic analysis. Novaranea courti n. sp. is found in the southeastern parts of Australia, including New South Wales, Victoria and Tasmania. Mature spiders are generally found between January and March, although some specimens were collected in April, June and November. Novaranea courti n. sp. appears to prefer forest habitats (e.g. Southern Beech (Nothofagus) forest and Eucalyptus/Casuarina woodland), but was also found in more open areas such as grassand heathland.